Detection of AmpC Beta-lactamases among Escherichia coli isolates at a tertiary care hospital in Karnataka - Smitha O. Bagali; B.V. Peerapur (Al Ameen Medical College, 2013)
Background & objective: AmpC β-lactamases are clinically significant because they may confer resistance to a wide variety of β-lactam drugs, including α-methoxy-β-lactams, such as cefoxitin, narrow-, expanded- and broad-spectrum cephalosporins, β-lactam-β-lactamase inhibitor combinations and aztreonam. Although reported with increasing frequency the true occurrence in different organisms remains unknown. The present study was conducted to determine the occurrence of AmpC β-lactamases among the clinical isolates of Escherichia coli. Methods: A total of 100 non-repeat clinical isolates obtained from urine, pus, sputum, blood and body fluids were taken. All the isolates were screened for AmpC β-lactamases by standard disc diffusion breakpoint for cefoxitin (30µg). Isolates with zone diameter less than 18 mm were tested for AmpC activity by AmpC disc test. Results: Of the 100 isolates that were tested, 30 yielded cefoxitin zone diameters less than 18 mm (screen positive). Production of AmpC β-lactamase was detected in 24 isolates by AmpC disc test. Conclusion: AmpC disc test can be used as a simple, convenient and rapid screening test for detection of AmpC β lactamase in clinical laboratories.